Partial Replacement with Menhaden Oil Improves Peripheral Neuropathy in High-Fat-Fed Low-Dose Streptozotocin Type 2 Diabetic Rat - Lawrence J. Coppey; Amey Holmes; Eric P. Davidson; Mark A. Yorek (Journal of Nutrition and Metabolism)
Aims. To determine the effect of partial replacement of a high-fat diet with menhaden oil on diabetic neuropathy in an animal model of type 2 diabetes. Materials and Methods. High-fat/low-dose streptozotocin diabetic rats were used to examine the influence of replacing 50% of the source of the high-fat diet (lard) with menhaden oil, a natural source of n-3 fatty acids, on diabetic neuropathy. Endpoints included analyses of glucose tolerance, fatty liver disease, serum and liver fatty acid composition, serum lipid and adiponectin levels, motor and sensory nerve conduction velocity, thermal sensitivity and innervation of the hindpaw. Results. Diabetic rats were insulin resistant and menhaden oil did not improve whole animal glucose utilization. Menhaden oil did not improve elevated HbA1C levels or serum lipid levels but serum levels of adiponectin were significantly increased and hepatic steatosis was significantly improved. Diabetic rats were thermal hypoalgesic, had reduced motor and sensory nerve conduction velocities and intraepidermal nerve fiber profiles were decreased in the hindpaw and these endpoints were significantly improved with menhaden oil. Conclusions. We found that enrichment of a high-fat diet with menhaden oil improved a number of endpoints associated with diabetic neuropathy.